Plan de marketing para el taller automotriz de vehículos livianos Tecni-Auto de la provincia de Loja - González Puertas, Claudio Renato (2015)
With advancing automotive technology is renewed and increases the local fleet, which needs trained maintenance services alternative to those of the manufacturers houses (Ford, Nissan, Chevrolet, etc.), the cost of labor with those that have them. An alternative service is an automotive workshop where engaged in vehicle repair, with trained personnel to attend any mechanical problem. The company Tecni-Auto, serves of automobile workshop in mechanical maintenance, electronics and repair of vehicles, the same as has competition from other similar workshops, has ongoing training for their employees, as well as has no position because that no advertising and promotions, leading to missed opportunities to attract potential clients and market positioning. For the above reasons the development of a marketing plan for the automotive workshop "Tecni-auto" for the province of Loja, it is proposed to improve the points described above innovating its image in the automotive market, which is develop analyzing the current situation of the company, defining its business philosophy, perform an external and internal analysis of the company, develop a SWOT and finally determine the strategic objectives At work in mention various methods and techniques of scientific research as the inductive were used to determine the overall conclusions based on data and facts obtained; deductive method that allowed information about the market of the service, determined the statistical method of quantitative analysis numerical data; Descriptive method to present, analyze and generalize the results; The literature method was used to collect scientific information about the subject matter. Besides observation techniques were used, applied to the Interview Workshop Manager Automotive Tecni-Auto Survey, applied 8, 319 employees and customers, allowing the analysis of internal factors by providing a clear view of reality Company and acceptance in front of customers. According to the matrix EFI obtained the result is 2.62, which means that the strengths of the company are good but that the weaknesses must be taken into account to improve the internal workshop with established strategies. It according to external analysis determined aspects: political, economic, social and technological, with Porter's 5 Forces, obtaining in the EFE Matrix totaling 2.93 which is higher than the average of 2.5, which should be designed strategies that maximize the effect of the opportunities and not to take into account the threats from the external environment. With data from internal and external SWOT matrix analysis was performed and then the high-impact matrix where the strategic objectives laid marketing strategies that allow the company to be more competitive were reflected, win a position and therefore more income for the company. The objectives are 1. Deploy computers with the latest 2. Design a publicity plan to publicize the services offered by the workshop in the city of Loja. 3. Apply a training plan to achieve staff provide quality service to customers and become a workshop leader in the market for subsequent years; this will have a total cost of $ 3.835,00With what it claims to be observed with great commitment the objectives for the workshop to develop through the growth and development of the market in an orderly, methodical and safe, with positive results for the same, reflected in higher profits. Finally, conclusions were raised based on the specific objectives of the project and then recommendations for both the company and future professionals